Effect of the addition of protected fat from palm oil to the diet of dairy sheep - Bianchi,Anderson Elias (2018)
ABSTRACT The objective of this study was to evaluate the effect of protected fat from palm oil on body weight and milk production and composition of lactating Lacaune ewes. Four treatments (0, 20, 40, and 60 g kg−1 as fed) of protected fat from palm oil were used to feed nine animals in each group. Isoproteic and isoenergetic diets were formulated and adjusted for each animal after milk weighing. Corn silage was used as roughage on the same proportion of concentrated to feed all animals. Milk samples were collected weekly for chemical analyses up to the seventh week of the lactation period and every other week after that until the end of the lactation period (182 days). Increased levels of protected fat in the diet of lactating ewes resulted in lower body weight gain and poor animal body condition. The production peak showed differences and was higher in the treatment of 40 g kg−1 of palm oil, but milk production during lactation was higher in animals that received 60 g kg−1 of protected fat supplementation. Animals fed 60 g kg−1 of protected fat showed the highest milk yield. We observed a positive linear effect on milk fat content, whereas the effect on milk protein, lactose, and nonfat solids was linearly negative after dairy sheep fed protected fat from palm oil. There were no changes in the amount (kg) of milk fat, protein, lactose, total solids, and nonfat solids in any of the treatments. Therefore, protected fat from palm oil is efficient to increase milk production and fat content.